2012 IEEE International Conference on RFID-Technologies and Applications (RFID-TA) 2012
DOI: 10.1109/rfid-ta.2012.6404509
|View full text |Cite
|
Sign up to set email alerts
|

An UWB-UHF semi-passive RFID System for localization and tracking applications

Abstract: We present a novel radio-frequency identification (RFID) system with capability of localization and tracking of passive or semi-passive tags. Localization and tracking features are enabled by backscatter modulation on ultra-wide bandwidth tag's antenna. A ultra-high frequency signal allows the wake-up of the tags enabling the reduction of energy consumption and ensuring compatibility with existing RFID systems. The overall system as well as the reader and tag architectures are introduced. The localization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Preliminary simulation results taking into account the hardware limitations, channel measured data, and interferences, have shown that the system is able to provide sub-meter accuracy in localization and tracking for different environments and are described in [16]. A full reader prototype has been realized and tested.…”
Section: Performance Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary simulation results taking into account the hardware limitations, channel measured data, and interferences, have shown that the system is able to provide sub-meter accuracy in localization and tracking for different environments and are described in [16]. A full reader prototype has been realized and tested.…”
Section: Performance Resultsmentioning
confidence: 99%
“…We then evaluate the simulation performance of the described receiver architecture in terms of localization error outage (LEO) [16]. A bi-dimensional reference scenario composed of a (10 × 10) m 2 room with four readers located at the corners is chosen, and tags are assumed to be static.…”
Section: Performance Resultsmentioning
confidence: 99%
“…a backscatter reflection, requiring simulations to mix in motion models or employ statistical tricks to attempt to model a complex, indoor UWB backscatter channel [17]. D'Errico et al further explore how to design a hybrid system with a conventional RFID frontend for wakeup and energy harvesting [10]. The Slocalization design is independent of energy frontend and amenable to such a hybrid design.…”
Section: Theoretical Systemsmentioning
confidence: 99%
“…Localization with Gen-2 ultra-high frequency (UHF) RFIDs is based on received signal strength indicator (RSSI), phase (also at different operating frequencies), or angle-of-arrival (AOA) measurements [8]- [14]. The ultra-wideband (UWB) technology [15]- [20] has been recently proposed for new generation RFID systems as it provides high ranging accuracy even in harsh propagation environments [21]- [25]. UWBbased RFID systems rely on the exploitation of the backscatter modulation 1 and the measurement of the time-of-arrival (TOA) of the backscattered signals [26]- [28].…”
Section: Introductionmentioning
confidence: 99%